(untitled) (Asian Business Research, 2017)
Purpose The purpose of this conceptual paper is to discuss the concept of bricolage. It defines the term bricolage and its personified form ‘bricoleur’. The paper attempts to identify some measures of bricolage that can assist to relate that concept to either growth of enterprises or their performance. The paper also relates bricoleurs to entrepreneurs. Lastly, the paper asks whether bricoleurs are born or made. Design/Methodology/Approach This is an exploratory paper on a new concept, which should be pursued in more detail in subsequent research. Sources of information are mainly journal articles identified by way of Google scholar. Conclusions point to a promising concept with potential to generate a number of articles on Botswana and surrounding countries. Findings Conceptually defining bricolage as separate from entrepreneurship is feasible, however, discussing related issues, like metrics, becomes fussy and difficult. Practical Implications Taking an extreme view that entrepreneurs, as currently defined, are failing could justify the concept of bricolage. However, common sense might lead one to conclude that, perhaps those failing are not really entrepreneurs. Bricolage can be seen, then as a trait of entrepreneurship. Originality/ Value The concept of bricolage is alien to African discourse. When presenting this paper at an African Conference in July 2017, the listeners were alarmed at the attempt to distinguish bricolage from entrepreneurship. Yet there is a wide-ranging debate in the world. These listeners, though experienced researchers in entrepreneurship, dismissed the concept in ignorance. Further research into the concept is justified.